Anticipating the ageing trajectories of superheroes in the Marvel cinematic universe. (13th December 2021) - Fox, Sarah T; Reid, Natasha; Tornvall, Ida; Weerasekera, Shavini; Gordon, Emily; Hubbard, Ruth E
Abstract : Ruth Hubbard and colleagues examine the personal traits and health behaviours of five of Marvel's superheroes and envisage the challenges this extraordinary cohort might experience during ageing